Balanced scorecard adoption in an institution of higher learning: a survey evidence - Fawzia, Farrah; Ramli, Aliza (2016)
The growing needs for quality in education had forced institutions of higher learning (IHL) to become more competitively responsible.In order to response to this competitive environment, IHL must adopt the most suitable performance measurement system in measuring their performances.The adoption of strategic performance measurement system would help IHL to realize significant cost saving, improve personal satisfactions and enhance organisational performances.Based on previous studies, Balanced Scorecard (BSC) is widely used as a strategic performance system in business sector, but few studies have reported BSC adoption in the education sector.Therefore, the objective of this paper is to determine the effectiveness of the adoption of BSC in assessing academicians’ performances in a selected IHL.This study focus on the leadership support and importance of academic qualifications in enhancing performance of academician and the university.Data were collected through survey questionnaire distributed to 70 academicians at the selected university.The survey resulted into 78.57% usable response rate.The descriptive results of this study revealed that the majority of academicians’ at the university extensively agree that the measurement used in the BSC which comprised of both financial and non-financial measurement are effective in assessing academicians’ performances.The findings from this study have advanced the literature on BSC in the education sector as well as, provided a better understanding of BSC as the performance measurement tool in assessing academicians’ performance.